Africa in global agricultural trade - Odjo, Sunday P.; Zaki, Chahir (International Food Policy Research Institute, 2020)
The objective of this chapter is to provide an overview of Africa’s trade structure and trade policy. We first analyze recent performance in different markets and identify changes in the composition and direction of trade. Second, we examine both tariffs and nontariff measures faced by African agricultural exporters, using several sources of data for trade barriers. Our main findings show that, while agricultural productivity is low, the European Union remains the primary destination for agricultural exports, although its share is constantly decreasing. At the product level, the top 10 agricultural export products represent 39 percent of Africa’s agricultural exports and include sesame seeds, black tea, cocoa paste, and fresh grapes. In terms of trade barriers, despite low tariffs faced by African economies, they are facing several nontariff measures (NTMs) ranging from sanitary and phytosanitary measures to conformity assessment and domestic support in other countries. Indeed, and in particular for agriculture products, unfair competition resulting from the domestic support in other countries affects the competitiveness of African countries’ exports.